Serial rivers. Le fleuve et le narrateur dans les Métamorphoses d’Ovide - Florian Racine (Pallas, 2024)
There are not many studies about river gods in Ovid’s Métamorphoses, and none are comprehensive. As shape-shifting deities, river gods perfectly fit for the poem’s subject. In Métamorphoses 8 and 9, Achelous plays the role of narrator. As a consequence, we might guess that Ovid gives him a reflexive function. Through this figure, he attempts to stand out from Virgil in order to show that his poetry is built on variation and self-citation, so that the poem seems inexhaustible.